2020
DOI: 10.2147/ott.s239979
|View full text |Cite
|
Sign up to set email alerts
|

<p>Interfering Human Papillomavirus E6/E7 Oncogenes in Cervical Cancer Cells Inhibits the Angiogenesis of Vascular Endothelial Cells via Increasing miR-377 in Cervical Cancer Cell-Derived Microvesicles</p>

Abstract: Background: The dysregulation of the human papillomavirus 18 E6 and E7 oncogenes plays a critical role in the angiogenesis of cervical cancer (CC), including the proliferation, migration, and tube formation of vascular endothelial cells. Interfering E6/E7 increases the number of CC cell-derived microvesicles (CC-MVs). Additionally, microRNAs (miRNAs) can modulate CC angiogenesis and can be encapsulated in MVs. Objective: We aim to investigate whether E6/E7 affects CC angiogenesis via regulating miRNAs in CC-MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…Besides, it was also confirmed in Figure 2 that E6 siRNA inhibits the VEGF-induced proliferation and migration, tube formation of HUVECs and tube formation. These results were consistent with those of Zhang et al, although the conditions of experiments were partially different [ 67 ]. These results suggested that HPV16 E6 is involved in VEGF-induced endothelial cell migration, proliferation and capillary-like tubular network formation.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, it was also confirmed in Figure 2 that E6 siRNA inhibits the VEGF-induced proliferation and migration, tube formation of HUVECs and tube formation. These results were consistent with those of Zhang et al, although the conditions of experiments were partially different [ 67 ]. These results suggested that HPV16 E6 is involved in VEGF-induced endothelial cell migration, proliferation and capillary-like tubular network formation.…”
Section: Discussionsupporting
confidence: 93%
“…Using a biomedical literature search platform, BEST (Lee et al, 2016 ), 14 genes were related to miRNA in the context of the HeLa cell line, cervical cancer, or ovarian cancer ( Supplementary Table 3 ). For example, the expression of LPAR2 was repressed by miR-377, and oncogenic processes such as cell proliferation or migration are known to be repressed by that inhibition mechanism (Zhang et al, 2020 ). As another example, ITGB1 was targeted by miR-183.…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNA miR-221-3p present in cervical cancer exosomes promoted angiogenic response [ 21 , 45 ]. Further, HPV oncogenes were shown to influence exosomal microRNA cargo by reducing level of anti-angiogenic miR-377 in microvesicles thereby promoting endothelial cell proliferation, migration, and tube formation [ 51 ]. In contrast, a recent study carried on HeLa exosomes showed breakdown of vascular integrity and endothelial cell permeability, essential for neo-angiogenic response, by triggering endoplasmic reticulum stress leading to metastasis.…”
Section: Discussionmentioning
confidence: 99%